Celtic art in Europe (Oxford ; Havertown, PA)
x, 372 s., [32] s. resim (renkli), plan, harita
Keywords: "The ancient Celtic world evokes debate, discussion, romanticism and mythicism. On the one hand it represents a specialist area of archaeological interest, on the other, it has a wide general appeal. The Celtic world is accessible through archaeology, history, linguistics and art history. Of these disciplines, art history offers the most direct message to a wider audience. This volume of 37 papers brings together a truly international group of pre-eminent specialists in the field of Celtic art and Celtic studies. It is a benchmark volume the like of which has not been seen since the publication of Paul Jacobsthal’s Early Celtic Art in 1944. The papers chart the history of attempts to understand Celtic art and argue for novel approaches in discussions spanning the whole of Continental Europe and the British Isles. This new body of international scholarship will give the reader a sense of the richness of the material and current debates. Artefacts of rich form and decoration, which we might call art, provide a most sensitive set of indicators of key areas of past societies, their power, politics and transformations. With its broad geographical scope, this volume offers a timely opportunity to re-assess contacts, context, transmission and meaning in Celtic art for understanding the development of European cultures, identities and economies in pre- and proto-history." --